Identity and Institutional Framework of Chilean Nurses in the Mid-Twentieth Century [Identidad E Institucionalidad de Las Enfermeras Chilenas en la Mitad del Siglo Xx] - Pavez-Lizarraga, A; Nunez-Carrasco, E (Universidad de Concepcion, 2016)
During the 70s and 80s Chile experienced a radical change in politics, social life and economy, causing profound changes in the country s social actors. For this research the social actor observed was nurses, with the aim of describing and connecting the historical record of the Chilean nurse with individual narratives, thus giving an identity account of the Chilean nurse before the 70s of XX century in Chile. Method: The research paradigm used was Constructivism, guided by the historiographical method, whose interpretation was guided by Claude Dubar; life stories and written records of secondary sources were also used. Results: What was obtained is the context surrounding the professionalization process of nurses in Chile as well as the stories and identity of nurses during the period prior to the 70s. Conclusion: It is possible to indicate that the identity of nurses before the 70s was characterized by the socialization of such identity within institutional spaces, then its defining action was given by the recognition of the urgency in the health intervention due to the precarious living conditions of the population; therefore, their action turns to the fulfillment of vital needs such as protection of the mother and newborn. Finally, the last step of their socialization process is the development of their own institutions, which establishes them within the Chilean public space, thus forming an identity as a community. © 2016, Universidad de Concepcion. All rights reserved.